Catheter ablation in Asian patients with atrial fibrillation and hypertrophic cardiomyopathy: electrophysiological characteristics of recurrence and long-term clinical outcomes - Lin, Chih-Hsien; Lin, Chin-Yu; Chung, Fa-Po; Lin, Yenn-Jiang; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Chao, Tze-Fan; Liao, Jo-Nan; Chang, Ting-Yung; Tuan, Ta-Chuan; Kuo, Ling; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Catheter ablation (CA) is a treatment strategy for atrial fibrillation (AF) in patients with hypertrophic cardiomyopathy (HCM). We investigated the electrophysiological characteristics of recurrence in a tertiary referral center and compared long-term clinical outcomes after CA therapy with patients who did not undergo CA. Methods: Patients with HCM and AF who underwent CA (group 1, n=60) or pharmacological treatment (group 2, n=298) between 2006 and 2021 were enrolled in this study. The baseline characteristics and electrophysiological characteristics of group 1 patients were examined to elucidate the reason for the recurrence of AF after CA therapy. The clinical results of the patients in Group 1 and Group 2 were compared using a propensity score (PS)-matched method. Results: The most common cause of recurrence was pulmonary vein reconnection (86.5%), followed by non-pulmonary vein triggers (40.5%), cavotricuspid isthmus flutter (29.7%), and atypical flutter (24.3%). Thyroid disease (HR, 14.713; P<0.01), diabetes (HR, 3.074; P=0.03), and non-paroxysmal AF (HR, 4.012; P=0.01); these factors independently predicted recurrence. After the first recurrence, patients who underwent repeat CA showed a better arrhythmia-free state (74.1%) than those who underwent drug escalation therapy (29.4%, P<0.01). After matching, PS-group 1 patients showed significantly better outcomes in all-cause mortality, heart failure hospitalization, and left atrial reverse remodeling than PS-group 2 patients. Conclusions: Patients who underwent CA showed better clinical outcomes than those who underwent drug therapy. The main predictors of recurrence were thyroid disease, diabetes, and non-paroxysmal AF.